(untitled) (Research, Society and Development, 2021)
This work reports the experience, during the elective discipline “Ações de promoção de saúde em Odontologia” of the Franciscan University of Santa Maria - RS. Through the discipline, remote actions were planned due to the COVID-19 pandemic. Meeting the demand raised by a Therapeutic Center (Centro Terapêutico - CT), students of Dentistry and Psychology, planned interprofessional actions to promote knowledge and new health habits. In order to maintain the link with users, despite the social distance from the pandemic, an explanatory video on oral health care was created and subsequently analyzed its correlations with the mental health of users. As a result of interprofessionality, autonomy in health care and formation of habits of this population emerged. It is concluded that despite the distance, the union of the students through shared knowledge allowed to create habits in health, maintaining the bond and contact with the community, respecting social distance.